Neoliberalism, Precarity, and Precariousness - Springveld, Niels (FRAME, Journal of Literary Studies, 2026)
The concepts of precarity and precariousness have become increasingly prominent in economic, philosophical, sociological, and activist discourse in recent decades. This article argues that the concepts allow for critiques of both economic and social injustice, and, as such, are of central importance to debates concerning the future of work, neoliberalism, and (state) violence. By synthesizing accounts of the development of neoliberalism and precarization with Judith Butler’s political ethics, this article attempts to do justice to demands for cultural and sexual equity on the one hand and economic equality on the other.